Perancangan Ulang Desain Website Mamnich sebagai Media Promosi dan Edukasi UMKM fashion Etnik - Krishana Ekka Angela; Taufik Murtono (Jurnal Bahasa Rupa, 2023)
Mamnich is a manufacturer who produce and sell various types of fashion with ethnic themes. Mamnich's promotion and transaction processes are mainly carried out through social media, e-commerce, and offline media, with the website being underutilized and having various shortcomings. However, maximizing website usage can provide various benefits, especially in this digital era. Maximizing this usage can be achieved by considering consumer and business owner opinions. Based on interviews with website users, Mamnich's website has various shortcomings in terms of appearance, functionality and ease of access, and content. Meanwhile, the owner expects Mamnich's website to support product promotion and serve as a platform for ethnic fashion education. Therefore, redesigning the Mamnich website is necessary to make it a promotional and educational platform that meets user needs and expectations. This research was conducted using design thinking method which consists of five steps, namely empathize, define, ideate, prototype, and test. Based on user interviews it can be concluded that the new Mamnich website prototype can maximize promotion, education, and meet user needs and desires.